Ship-based Trackline Geophysical Data (MGD77) from the Amundsen Sea, Antarctica acquired during the Nathaniel B. Palmer expedition NBP0702 (2007) (IEDA: Marine-Geo Digital Library, 2007)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler during Nathaniel B. Palmer expedition NBP0702 conducted in 2007 (Chief Scientist: Dr. Stan Jacobs; Investigator(s): Dr. Frank Nitsche). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise. Data were acquired as part of the project(s): The Amundsen Continental Shelf and the Antarctic Ice Sheet, and funding was provided by NSF grant(s): ANT04-40775